Pengaruh Efektivitas Dana Bantuan Usaha Mikro (BPUM), Penggunaan E-Commerce, Dan Modal Usaha Terhadap Pendapatan Usaha Mikro, Kecil Dan Menengah (UMKM) Se-Kecamatan Denpasar Timur - Mahayuni, Ni Luh Ayu; Padnyawati, Kadek Dewi; Ayu, Putu Cita (Hita Akuntansi dan Keuangan, 2024)
This investigate points to decide the impact of Miniaturized scale Commerce Help Reserves (BPUM), the utilize of e-commerce, trade capital on the wage of smaller scale, little and medium undertakings (UMKM) all through East Denpasar Locale. The populace in this think about were all MSMEs in East Denpasar Locale with a add up to of 3,961 MSMEs. Utilizing the Slovin equation, the test gotten in this ponder was 100 MSMEs, which were decided utilizing irregular examining procedures and tried utilizing 3 tests which included investigate tests (legitimacy test and unwavering quality test), classical suspicion test (ordinariness test, multicollinearity test, and heteroscedasticity test) and show possibility test (F test, coefficient of assurance (R2), t factual test.The comes about of this inquire about appear that Small scale Trade Help Stores (BPUM), Utilize of E-Commerce, Trade Capital have a positive impact on the Salary of Miniaturized scale, Little and Medium Undertakings (MSMEs) all through the East Denpasar Locale. Looking at the investigate comes about, within the future all MSMEs in East Denpasar District must be able to extend their monetary pay by going to preparing related to the significance of bookkeeping for smaller scale businesses, utilizing online promoting innovation for MSMEs, expanding development and item creation in arrange to grow the showcase for MSMEs. MSME performing artists